2020
DOI: 10.1111/jdi.13366
|View full text |Cite
|
Sign up to set email alerts
|

Significance of body mass index for diagnosing sarcopenia is equivalent to slow gait speed in Japanese individuals with type 2 diabetes: Cross‐sectional study using outpatient clinical data

Abstract: Aims/Introduction This study examined the association between body mass index (BMI) and the risk of sarcopenia in Japanese type 2 diabetes patients. Materials and Methods Patients with type 2 diabetes who visited an outpatient clinic comprised the study’s participants. Sarcopenia was defined using the definition of the Asian Working Group for Sarcopenia 2014. The area under the curve was examined for the presence of sarcopenia based on the receiver operating characteristic curve of BMI. Results Among 1,137 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, since sarcopenia was defined according to The Asian Working Group for Sarcopenia (AWGS) in this study, relationship between BMI and hand grip strength was not investigated, and the number of patients with only low hand grip strength was not determined. In a study conducted with type 2 DM patients in the outpatient setting, BMI with a cut-off point of 24.4 kg / m 2 predicted sarcopenia as much as walking speed (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since sarcopenia was defined according to The Asian Working Group for Sarcopenia (AWGS) in this study, relationship between BMI and hand grip strength was not investigated, and the number of patients with only low hand grip strength was not determined. In a study conducted with type 2 DM patients in the outpatient setting, BMI with a cut-off point of 24.4 kg / m 2 predicted sarcopenia as much as walking speed (24).…”
Section: Discussionmentioning
confidence: 99%
“…Probable sarcopenia was found in 69.1% of patients with DM, while sarcopenia was found in only 1.6% of patients with DM. In the literature, the prevalence of sarcopenia varies between 12% and 18% in older patients with type 2 DM according to the AWGS and increases to 40% in DM patients aged older than 80 years (23,24,26). The prevalence of sarcopenia varies between 2% and 4% according to EWGSOP2.…”
Section: Discussionmentioning
confidence: 99%
“…BMI <24 kg/m 2 will increase the risk of sarcopenia. And the research [39] also showed that BMI may be a practical index for screening sarcopenia, and can be used as a substitute index of gait speed in the diagnosis of sarcopenia to a certain extent.…”
Section: Influencing Factors Related To Sarcopenia In Patients With T2dmmentioning
confidence: 99%
“…Type 2 diabetes mellitus is a common cause of sarcopenia, with the risk of sarcopenia being threefold higher compared with individuals without diabetes 8 . Certain features, including age, sex, body mass index (BMI), glycemic control and a high body fat percentage are risk factors for sarcopenia in diabetes patients 9 , 10 , 11 , 12 . Nevertheless, other causes of sarcopenia in patients with type 2 diabetes mellitus are not well established.…”
Section: Introductionmentioning
confidence: 99%